Media Interaktif Adobe Flash CS6 dengan Model Dart dalam Pembelajaran Bahasa Arab Di Era Pandemi Covid-19 - Muhammad Irsyad (Thawalib: Jurnal Kependidikan Islam, 2020)
In modern times there are various ways of learning, one of which is learning through Adobe Flash CS6. Learning Arabic will be done using Adobe Flash CS6 interactive media, especially during the Covid 19 virus pandemic as it is today. This type of research is library research, and researchers get data in this study in the form of primary data sources obtained from a book written by Ichwan K entitled Membuat Media Pembelajaran degan Adobe Flash CS6 published in 2015 by CV Andi Offset, a book written by Deni Darmawan entitled Inovasi Pendidikan published in 2012 by PT Remaja Rosdakarya, and Journals written by Poppy Kamalia Devi entitled DART dalam Pembelajaran IPA. And secondary data in this study researchers obtained from reading books, articles, and literature in the form of printed or electronic, as well as earlier studies on the goals and objects of research. This research aims to help educators to be able to create learning media using Adobe Flash CS 6 so that it will be easier for educators and students to carry out the learning process more deeply. This is because adobe flash CS 6 interactive media has two-way communication between students and the media, has direct feedback, there is input data, including physical and mental activities, there is a mouse click or mouse enter so that students can learn by active and independent when using this interactive media